Influence of the constituent morpheme boundary on compound word access. - Taikh, Alexander; Gagné, Christina L.; Spalding, Thomas L. (Memory & Cognition, 2024)
Embedded morphemes are thought to become available during the processing of multi-morphemic words, and impact access to the whole word. According to the edge-aligned embedded word activation theory Grainger & Beyersmann, (2017), embedded morphemes receive activation when the whole word can be decomposed into constituent morphemes. Thus, interfering with morphological decomposition also interferes with access to the embedded morphemes. Numerous studies have examined the effects of interfering with boundary and constituent-internal letters on morphological decomposition by comparing the effect of transposing letters at the morphemic boundary to constituent-internal letters. These studies, which report inconsistent findings, have typically used derived multi-morphemic words (e.g., cleaner), and sometimes use a control replacement letter condition that is not matched to the transposed letter conditions in terms of location. Across five experiments, we test the edge-aligned activation theory by examining the effects of replacing and transposing boundary and constituent-internal letters of compounds. Our findings suggest that replacing boundary letters interferes with access to both embedded constituents, while replacing constituent-internal letters still allows for access to the unaltered constituent, thus compensating for the interference in the altered constituent. Our findings are consistent with the edge-aligned theory with respect to letter replacement, and also imply that letter replacement must match the position of letter transposition when it is used as a control condition.